Shoulder extension strength: a potential risk factor for shoulder pain in young swimmers? - McLaine, S. J.; Bird, M.-L.; Ginn, K. A.; Hartley, T.; Fell, J. W. (Journal of Science and Medicine in Sport, 2019)
Objectives: To determine the relationship and predictive value of isometric shoulder strength in the development of shoulder pain in young swimmers. Design: Prospective, cohort study. Methods: Shoulder flexion, extension, external and internal rotation strength tests were performed in elevation on 85 swimmers (14-20 years; 48 females) without current shoulder pain using a hand-held dynamometer. Following testing, swimmers were emailed questionnaires to determine if significant shoulder pain developed within 24 months subsequent to testing. The differences between shoulders that did and did not develop pain and the predictive ability of shoulder strength and strength ratios were investigated using Mann Whitney U tests and receiver operating characteristic curves. Results: Thirty-seven swimmers (47%) returned questionnaires and 18 reported shoulder pain. A comparison of individual shoulders (27 with pain reported and 47 without) determined that shoulder extension strength was lower and flexion:extension strength ratio was higher for male swimmers (n = 36 shoulders) who reported shoulder pain compared to those who did not (p = 0.04). The predictive value of extension strength was fair (0.72; p = 0.03) for males with a cut-off value for extension strength calculated at 13.5% body mass. There were no differences between the two groups in shoulder rotation strength, age, training hours or previous pain history. Conclusions: Shoulder extension strength, a functional test for swimmers, was associated with and predictive of the development of shoulder pain in male swimmers. Low shoulder extension strength may be a risk factor for the development of shoulder pain in swimmers, proposing a direction for injury prevention and future investigation.